1979
DOI: 10.1093/infdis/140.2.222
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Observations on Giardiasis in a Mouse Model. II. Endosymbiosis and Organelle Distribution in Giardia muris and Giardia lamblia

Abstract: Ultrastructural observations of Giardia muris in a mouse model revealed endosymbiotic microbes not previously reported in Giardia. Endosymbionts 240--360 nm wide, 600--1,400 nm long, and with an internal structure similar to that of bacilli were not seen entering Giardia but were found and appeared to divide within Giardia. No evidence was found of digestion of the endosymbionts by the giardia host in either the trophozoite or the cyst form. Endosymbionts were concentrated centrally around the nuclear area and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…Some eukaryotic taxa have been shown to be intimately associated with bacteria in the form of endosymbioses, including Trichomonas vaginalis (Rappelli et al, 2001), Giardia (Nemanic et al, 1979), and Entamoeba (Ahmad, 1971). Trichomonas vaginalis is a major vaginal pathogen infecting 180 million people worldwide each year and causes vaginal inflammation as well as problems with pregnancy (Soper, 2004).…”
Section: Interplay Between Bacteria and Eukaryotesmentioning
confidence: 99%
“…Some eukaryotic taxa have been shown to be intimately associated with bacteria in the form of endosymbioses, including Trichomonas vaginalis (Rappelli et al, 2001), Giardia (Nemanic et al, 1979), and Entamoeba (Ahmad, 1971). Trichomonas vaginalis is a major vaginal pathogen infecting 180 million people worldwide each year and causes vaginal inflammation as well as problems with pregnancy (Soper, 2004).…”
Section: Interplay Between Bacteria and Eukaryotesmentioning
confidence: 99%
“…Suc h a fact coul d explain th e lac k o f any mirror-imag e attachmen t o f th e striate d disk t o th e intestin e i n case s o f huma n biopsies 11 . Previous publication s di d no t provid e evidence o f ultrastructura l difference s betwee n Giardia muri s an d Giardi u lambli a trophozoites 12 , althoug h KULD A & NORYNKOVÁ* i n a revie w abou t Giardi a ultrastructure, hav e suggested that th e marginal plates i n Giardi a intestinalis ar e les s develope d than i n Giardia muris.…”
Section: According T O Holbertonmentioning
confidence: 98%
“…al. 12 wer e unabl e t o sho w difference s betwee n trophozoites o f Giardi a muri s fro m mic e an d those of Giardi a lamblia fro m man.…”
Section: Introductionmentioning
confidence: 96%
“…In this case, the surface saccharide ligands of the superficial membrane are altered by the presence of intracellular bacterial symbionts, so that in axenic protozoa cured of their endosymbionts, a possible decrease in adhesion or in invasive abilities can be observed (Phillips, 1973; Dwyer and Chang, 1976). Also in Giardia , in the past decade, ultrastructural observations of Giardia muris in a murine model revealed endosymbiotic microbes which, according to the authors, could be related to variation in the trophozoite pathogenicity, metabolism, range of infectivity, antigenic surface characteristics, and host specificity (Nemanic et al, 1979). More recently, the presence of Giardia trophozoites harboring peripheral bacterial endosymbionts was also demonstrated by El-Shewy and Eid (2005).…”
Section: Protozoansmentioning
confidence: 99%